The effectiveness of Qanun Aceh No. 9/2004 and Qanun Aceh No 6. 2014 in solving khalwat cases in Sawang District - Fauzah Nur Aksa; Herinawati Herinawati; Muhammad Nasir; Rahmatul Amna (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
This study aims to find out and explain the settlement of khalwat cases carried out in Sawang sub-district, the causes of which there are still many occurrences of khalwat and the effectiveness of Qanun Number 9 of 2008 concerning the Development of Customary and Customary Life and Aceh Qanun Number 6 of 2014 concerning Jinayat Law in the settlement of khalwat cases in Sawang District. This study uses empirical research methods and empirical juridical approaches. The data were obtained through field research and library research. Data analysis was carried out qualitatively. The results of the study show that the process of resolving khalwat cases begins with the arrest, summons to the family, decision making and implementation of the decision. Settlements for khalwat cases were resolved jointly according to custom, and the punish ments given were relatively light such as giving advice, reprimands, apologies, sayam, dhiyat, fines, compensation, ostracismby the community, expulsion from the gampong community or revocation of titles and soon. There are still many cases of khalwat, namely the lack of attention and control from the family, the lack of family knowledge about the dangers of khalwat, unstoppabledesires, the lack of public knowledge of the law in Sawang sub-district, the existence of tourist objects that allow khalwat to emerge, many families of khalwat perpetrators who blaming customary apparatus forgiving punishments, and the lack of legal socialization in gampong. The implementation of Qanun Number 6 of 2014 concerning Jinayat Law, namely concerning the authority of the customary court in handling khalwat cases which refers to Qanun Number 9 of 2008 concerning the Development of Customary and Customary Life has not been effective, as evidenced by the non-fulfillment of elements measuring the effectiveness of law enforcement.